Experimental study on preparation of mine-used filling cementitious material from multi-source coal-based solid wastes - Zhifei LIU; Wei WU; Zhongwei BI; Xingyu FU; Yeqing LANG; Qingli HOU; Xinguo JIA (Meikuang Anquan)
In order to reduce the cost of coal mine filling and mining, and achieve the synergistic utilization of multi-source coal based solid waste, special filling cementitious material is prepared using solid waste such as fly ash, gasification slag, and desulfurization gypsum as the main raw materials. By conducting orthogonal test, the optimal ratio of each component in the cementitious material was determined, and the Tesser five-step method was used to study the occurrence and leaching characteristics of heavy metal elements in the cementitious material. The results show that the optimal ratio of cementitious material, fly ash∶furnace bottom ash∶gasification slag∶cement clinker∶desulfurization gypsum∶quicklime, is 39.1%∶23.4%∶15.6%∶10.9%∶4.7%∶6.3%; after curing for 7 days, the hydration products mainly exist in the form of needles and are connected by flocculent and filamentous products; the curing age reaches 28 days, and the hydration products mainly exist in the form of clumps or blocks. The hydration products bind tightly, and the net slurry strength of the cementitious material reaches 1.83 MPa and 2.44 MPa at 7 and 28 days, respectively. The filling cementitious material prepared from solid waste such as fly ash can effectively solidify heavy metals and has no risk of heavy metal pollution to the underground environment.